The Ethiopian Orthodox Tewahedo Church Canon of the Scriptures Neither Open nor Closed - Asale, Bruk Ayele (2016)
Traditionally, the Ethiopian Orthodox Tewahedo Church (EOTC) holds that its canon of the Scriptures comprises eighty-one books of the Old and New Testaments. However, which books comprise this list remains obscure and the very little research executed so far on the topic is both insufficient and misleading. This paper critically investigates if there has ever been a closed canon in the EOTC. It further critically engages with the notion and concept of the term “canon” and/or the Scripture(s). The theoretical framework applicable to this study is a history of reception approach as the study focuses on the history of reception, collection, translation, and transmission of the Scriptures in the Ethiopian Church. Methodologically, this study applies both library readings and fieldwork and the main tool employed in collecting data is qualitative interviews. In addition, insights from Ethiopian literature that have been neglected or that were earlier inaccessible are used. Finally, the study tries to prove that not only the canon of the EOTC, but also its concept in this church is very loose; it is possible to conclude that the canon of the EOTC is neither open nor closed.
Keywords: Ethiopian Orthodox Tewahedo Church (EOTC); Ge‘ez; Scripture; Biblical Canon; Reception History